Use of electronic devices by the medical students of UniKL-RCMP, Malaysia, and its influence on academic performances - Mainul, Haque; A. T. M. Emdadul, Haque; Sandheep, Sugathan (2016)
Background: The availability and the use of electronic devices among the students of higher education have been continuing to grow. The devices connect the users to the world instantly, allow access to information, and enable interactivity with others. The uses of these devices are playing an important role, especially in their academic lives.